Pre-prepared Microemulsion Flooding in Enhanced Oil Recovery: A Review - Jeirani, Z.; Mohamed Jan, B.; Si Ali, B.; See, C.H.; Saphanuchart, W. (Taylor & Francis, 2014)
It is evident that one of the important applications of microemulsions is in enhanced oil recovery (EOR) process due to its unique properties such as ultra-low interfacial tension. The injection of microemulsion slug reduces the interfacial tension between the crude oil and reservoir brine, which leads to mobilization of substantial fraction of residual oil. In general microemulsion flooding is classified into two distinct categories, pre-prepared and in situ prepared, depending on its preparation method. The authors present a detailed discussion of microemulsion preparation and summarizes major articles on pre-prepared microemulsion flooding in EOR processes. Their review opens new horizons for the future researches on pre-prepared microemulsion flooding in EOR processes by organizing the literature data and comparing them.